Children With Asthma Have Impaired Innate Immunity and Increased Numbers of Type 2 Innate Lymphoid Cells Compared With Healthy Controls - Hosseini, Banafshe; Berthon, Bronwyn S.; Starkey, Malcolm R.; Collison, Adam; McLoughlin, Rebecca F.; Williams, Evan J.; Nichol, Kristy; Wark, Peter AB.; Jensen, Megan E.; Da Silva Sena, Carla Rebeca; Baines, Katherine J.; Mattes, Joerg; et al. (Frontiers in Immunology, 2021)
Background Asthma is the most frequent cause of hospitalisation among children; however, little is known regarding the effects of asthma on immune responses in children. Objective The present study aimed to evaluate cytokine responses of peripheral blood mononuclear cells (PBMCs), PBMC composition and lung function in children with and without asthma. Methods Using a case-control design, we compared 48 children with asthma aged 3-11 years with 14 age-matched healthy controls. PBMC composition and cytokine production including interferon (IFN)-γ, interleukin (IL)-1β, IL-5 and lL-6 following stimulation with rhinovirus-1B (RV1B), house dust mite (HDM) and lipopolysaccharide (LPS) were measured. Lung function was assessed using impulse oscillometry and nitrogen multiple breath washout. Results The frequency of group 2 innate lymphoid cells were significantly higher in asthmatics and PBMCs from asthmatics had deficient IFN-γ production in response to both RV1B and LPS compared with controls (P<0.01). RV1B-induced IL-1β response and HDM-stimulated IL-5 production was higher in asthmatics than controls (P<0.05). In contrast, IL-1β and IL-6 were significantly reduced in response to HDM and LPS in asthmatics compared to controls (P<0.05). Children with asthma also had reduced pulmonary function, indicated by lower respiratory reactance as well as higher area of-reactance and lung clearance index values compared with controls (P<0.05). Conclusion Our study indicates that children with asthma have a reduced lung function in concert with impaired immune responses and altered immune cell subsets. Improving our understanding of immune responses to viral and bacterial infection in childhood asthma can help to tailor management of the disease.